Praxis of performance measurement in public-private partnerships: Moving beyond the iron triangle - Liu, Henry; Love, Peter; Smith, J.; Matthews, Jane; Sing, C. (ASCE, 2016)
© 2016 American Society of Civil Engineers.An effective and efficient performance measurement is deemed to be pivotal for ensuring owners' and stakeholders' needs are being met throughout a project's lifecycle. To determine the nature of performance measurement in Australian public-private partnerships (PPPs), an interpretivist approach that utilized semistructured interviews was undertaken in the State of Western Australia. A total of 25 interviews were conducted with key stakeholders and it was revealed that there was a proclivity for performance measurements during design and construction to focus on traditional ex ante and ex post evaluations that were aligned to the conventional iron triangle: time, cost, and quality (TCQ). However, there was widespread consensus among the interviewees that the traditional TCQ approach was too simplistic to capture the inherent complexities associated with social infrastructure PPPs. In addressing this issue the analysis indicates that process-based lifecycle performance measurement that strategically places an emphasis on value for money (VfM) should be introduced into PPPs to replace traditional ex ante and ex post evaluations. It is suggested that this type of measurement can be integrated with a broader VfM assessment and a series of key performance indicators to enable the public and private sectors to improve their performance throughout a project's lifecycle. The empirical analysis provides the foundations for developing a performance measurement that can ensure assets are future proofed over their lifecycles.